Attentional Networks and Consciousness - Posner, Michael (Frontiers in Psychology, 2012)
The term consciousness is an important one in the vernacular of the western literature in many fields. It is no wonder that scientists have assumed that consciousness will be found as a component of the human brain and that we will come to understand its neural basis. However, there is rather little in common between consciousness as the neurologist would use it to diagnose the vegetative state, how the feminist would use it to support raising male consciousness of the economic plight of women and as the philosopher would use it when defining the really hard question of the subjective state of awareness induced by sensory qualities. When faced with this kind of problem it is usual to subdivide the term into more manageable perhaps partly operational definitions. Three meanings that capture aspects of consciousness are: (1) the neurology of the state of mind allowing coherent orientation to time and place (2) the selection of sensory or memorial information for awareness and (3) the voluntary control over overt responses. In each of these cases the mechanisms of consciousness overlap with one or more of the attentional networks that have been studied with the methods of cognitive neuroscience. In this paper we explore t